EKSPLORASI SERANGGA PADA TANAMAN BAWANG MERAH YANG DITUMPANGSARIKAN DENGAN CABAI MERAH (STUDI KASUS DI KECAMATAN GRONG GRONG KABUPATEN PIDIE) - Amar, Aidil; Fridayati, Diah; Marlina, Marlina; Fatmala, Nanda; Fauza, Saniar; Irwansyah, Irwansyah (Universitas Suryakancana, 2024)
Intercropping is a method that is widely used by farmers, this is because this method allows farmers to plant not just one type of plant but more. There are many advantages of this tumpeng sari system, such as increased plant production and optimal use of land. In plants, a diversity of insects appear that live and visit because of the influence of this tumpeng sari system. The aim of the research was to describe the types of insects found on shallot plants intercropped with red chilies. The purposive sampling survey method was used in the research, which was practically carried out on a stretch of land with red onions intercropped with red chilies. The research shows the results that insects trapped in shallot fields intercropped with chilies consist of 10 orders and 47 families, the order Araneae, the order Blatodea, the order Coleoptera, the order Dermaptera, the order Hemiptera, the order Diptera, the order Hymenoptera, the order Isoptera, the order Lepidoptera, the order Mantodea, while for There are two natural enemies of parasitoids, namely the order Hymenoptera, Diptera, for predatory insects the order found is the order Mantodea, order Orthoptera, order Lepidoptera, order, Hymenoptera, order Hemiptera, order Diptera, order Dermaptera, order Coleoptera order Araneae, while the order herbivorous insects found were the order Orthoptera, order Hemiptera, order Diptera, order Lepidoptera, order Coleoptera, a group of parasitoid insects with the highest number of individuals from the families Ichneumonidae and Braconidae, a group of predatory insects with the highest number of individuals from the family Reduviidae, and formicidae, a group of herbivorous insects with the highest number of individuals. high number of individuals from the Orthoptera family